Monitoring Kecepatan dan Arah Angin Pada Jembatan Suramadu Menggunakan SMS Gate Away Berbasis Microcontroller - Taufik, Imam; Huda, Mochammad Syamsul; Muharom, Syahri; Mollah, Moch Kalam; Munir, Misbahul; Firmansyah, Riza Agung; Septyan, Mamat (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2024)
This research aims to develop a system for monitoring wind speed and direction on the Suramadu Bridge using an SMS Gateway based on a microcontroller. The system is designed to monitor wind conditions in real time and provide accurate information to users. Wind speed and direction sensors are installed on the bridge and connected to a microcontroller. Data obtained from the sensors is processed by the microcontroller and sent via an SMS Gateway for user access. Testing is conducted to ensure the system accuracy in measuring wind speed and direction, as well as its ability to deliver timely information via SMS. The results show that this system is effective in monitoring wind conditions on the Suramadu Bridge with adequate accuracy and accessibility of information through the SMS Gateway. This research contributes to the development of environmental monitoring systems that can be used in risk management and infrastructure security.